HUBUNGAN BERAT BAYI LAHIR RENDAH, KETUBAN PECAH DINI DAN PERSALIANAN PREMATUR DENGAN KEJADIAN SEPSIS NEONATORUM - Rizki, Merisa; Afrika, Eka (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background: Sepsis is a clinical syndrome with the presence of Systemic Inflammatory Response Syndrome (SIRS) and infection. Sepsis is a continuous process starting from infection, SIRS, severe sepsis, septic shock/shock, multiorgan dysfunction, and finally death.Objective: To determine the relationship between low birth weight, premature rupture of membranes, and preterm labor with the occurrence of neonatal sepsis. Method: The method used is a quantitative research method, using an observational analytic study with a cross sectional research approach, where the data collection of the independent variable and the dependent variable is taken at the same time.Results: Based on the results showed that there was a significant relationship between low birth weight, premature rupture of membranes, premature labor and neonatal sepsis, the statistical test results obtained a p-value of 0.001 which means that there was a relationship between birth weight and neonatal sepsis.Conclusion: There is a relationship between low birth weight,premature rupture of membranes, premature labor and the incidence of neonatal sepsis. Key words:Low birth weight, premature rupture of membranes, premature labor and neonatal sepsis